A Possible Mechanism on the Detachment Between a Subauroral Proton Arc and the Auroral Oval. Issue 2 (15th February 2021) - Zhou, Su; Luan, Xiaoli; Burch, J. L.; Yao, Zhonghua; Han, De‐Sheng; Tian, Chenjing; Chen, Yuqing; Zhang, Jin; Yu, Xiaoyan; Dai, Tianjun
Abstract: Subauroral proton arcs are a type of terrestrial auroral phenomena, which are often detached equatorially from the auroral oval. This work presents evolution of a subauroral proton arc using observations of the Special Sensor Ultraviolet Spectrographic Imager and Special Sensor J (SSJ) on board Defense Meteorological Satellite Program (DMSP) spacecraft. The arc was observed in the afternoon sector and was located within 60°–70° geomagnetic latitude during the recovery phase of a moderate magnetic storm with the minimum SYM‐H index of −55 nT. Particle measurements from DMSP F17/SSJ indicate that the arc was detached from the normal oval and produced by energetic ring current ions with energies above 10 keV. These energetic ions were likely scattered into the magnetic loss cone by electromagnetic ion cyclotron waves in the frequency range between 0.1 and 0.5 Hz, as confirmed by Pc1 waves derived from the observations of a ground station. Continuous auroral observations directly show that the subauroral proton arc was detached from the oval during evolution. Following a northward interplanetary magnetic field turning, the auroral oval moved toward higher latitudes. We propose that the equatorward edge of the auroral oval is less influenced by the convection electric field, and thus moves more slowly than the poleward edge. This mechanism is proposed for producing a separation between the equatorward and poleward parts of the auroral oval, with the former evolving into the subauroral proton arc. Key Points: The equatorward edge of the auroral oval evolved into a subauroral proton arc due to a northward interplanetary magnetic field turning The subauroral proton arc was produced predominantly by energetic ring current ions likely scattered by electromagnetic ion cyclotron waves Plasma drift velocity is low at subauroral region, suggesting the convection electric field being a reason for the detachment of the arc